BACTERIAL PROFILE AND ANTIBIOTIC SUSCEPTIBILITY TEST AMONG DIABETES MELLITUS PATIENTS WITH GANGRENE IN SURABAYA - Qona`ah, Imro`atul; Sundari, Aliyah Siti; Wahyuni, Ratna; Indriati, Dwi Wahyu (Journal of Vocational Health Studies, 2024)
Background: Gangrene is a severe complication of damaged tissue that can occur in people with Diabetes Mellitus (DM), putting them at risk for bacterial infection. A pus culture can show diabetic gangrene patients' infecting bacteria. Purpose: Determine the prevalence of infection-causing bacteria and antibiotic sensitivity tests in diabetic gangrene patients at Haji Regional General Hospital, East Java Province, for January-December 2021. Method: The method used in this study is observational analytical cross-sectional, which is based on secondary data and is analyzed using the percentage formula and Chi-Square test. Result: The data obtained from 39 patients revealed 29 (74.4%) positive patients for bacterial infection. The Gram-negative bacteria was found to cause infection more frequently (72.41%) than the Gram-positive bacteria (27.59%). The prevalence of Gram-negative bacteria species most frequently from Escherichia coli (ESBL) 13.79% (4/29), Klebsiella pneumoniae 10.35% (3/29), Proteus mirabilis 10.35% (3/29). While the dominant Gram-positive bacteria a Methicillin-Resistant Staphylococcus aureus (MRSA) 10.35% (3/29). The antibiotic sensitivity test showed that Gram-negative group were susceptible to ertapenem, meropenem, amikacin, gentamicin, and piperacillin tazobactam while resistant to ampicillin and cefazolin. The antibiotic sensitivity tests showed that the Gram-positive group was susceptible to linezolid, vancomycin, and tigecycline while resistant to tetracycline and ciprofloxacin. Conclusion: It is important to screen the bacterial profile causing gangrene and their antibiotic susceptibility pattern in DM patients in order to give proper treatment to DM patients.